PENGGUNAAN ISTILAH BUDAYA BALI PADA MEDIA PROMOSI PARIWISATA BERBAHASA INGGRIS KOTA DENPASAR - Ekasani, Kadek Ayu; Supartini, Ni Luh (LP2M IKIP PGRI Bali, 2018)
The purpose of this study is to look at the category of Balinese culture terms in English media tourism promotion in Denpasar City, and the purpose of using the term in tourism promotion media published by the Tourism Department of Denpasar City. The method used in this study is a qualitative descriptive method where the data studied are words and phrases about the term Balinese culture. Qualitative methods produce descriptive data both in the form of written and verbal expressions of the people and behaviors observed. The results of the data analysis are presented with informal methods where the results of the data analysis are presented using word threads, sentences, and technical terms to formulate and describe any research issues. From the results of research there are 3 types of categories of Balinese culture, namely the category of material culture, the category of social culture, and the category of tradition and concept. While the purpose of the Tourism Department of Denpasar City uses the term Balinese culture in the promotion media of English-language tourism in Denpasar is to preserve Bali culture and introduce Bali culture abroad.